Laporan hasil Rapat Kerja, Pengembangan GBPP Ilmu-Ilmu Sosial SMP, SMA, SPG/SGO, SGPLB, Hotel Cibogo, 3 s.d. 5 Januari 1985 (Departemen Pendidikan dan Kebudayaan, Badan Penelitian dan Pengembangan Pendidikan dan Kebudayaan, Pusat Pengembangan Kurikulum dan Sarana Pendidikan, 1985)
On the development of educational programs in social sciences for lementary, junior and senior high schools, teacher's training, etc., results of a meeting.